APPLICATION OF THE GEOELECTRIC METHOD TO IDENTIFY SUBSCRIPTION FAULT IN SAMBELIA DISTRICT DUE TO THE 2018 EARTHQUAKE - Muliana, Winda; Hiden, Hiden; Syamsuddin, Syamsuddin (Indonesian Physical Review, 2023)
Earthquake activity triggers fault activity such as what happened on Lombok Island. Therefore, it is necessary to carry out research related to the existence of faults by identifying the type of fault, so that the risk of danger can be overcome before an earthquake occurs, especially in Sambelia District, East Lombok Regency. The purpose of this research is to find out whether there is a fault in the research area caused by the 2018 earthquake and to analyze its geometry in Sambelia District, East Lombok Regency. Data acquisition using the Geoelectric resistivity Wenner configuration method . The results of the research on 12 tracks with a length of 230 meters each track, on each track there are 3 rock layers in 2D cross section. Based on the inversion results, of the twelve main rock types that dominate include clay, sandstone, and breccia with a depth of up to 40 meters, with the highest elevation of 168 meters above ground level. The existence of faults on all tracks has a depth ranging from 16.75 meters. In the research area, many fractures were found which were possibly caused by the 2018 earthquake activity which led to the finding of faults on each trajectory. The type of rock that indicates the presence of a fault is breccia rock that experiences discontinuity with a resistivity value of (7.33 – 82.1) ohm-m and is filled or covered by sedimentary deposit rocks, namely clay and sandy loam with a resistivity value of (0.483 – 3.62) ohm-m. The faults in Sambelia District are micro-faults forming a line through exposed fractures extending to the northeast. The average geometry of the fault is: 15 meters wide, 77° average slope and 37° northeast strake .